Cumulative metabolic stress (microfilarial infection + moult) constrains the expression of carotenoid-based honest signals in breeding male village weavers (Ploceus cucullatus) of Amurum Forest Reserve, Nigeria - Felix A. Andong; Olufemi Olasoji; Abdifatah Ahmed A. Afyare; Ezekiel S. Mayowa; Praise O. Nwanozie; Emmanuel E. Osayi; Ruth A. Agyo; Vincent C. Ejere (PLoS ONE, 2026)
In wild birds, the breeding season involves a convergence of metabolically demanding life-history stages, including reproduction, moult, and immune defense. We investigated the relationships between microfilarial infection, moult, redox homeostasis, and plumage quality in breeding male village weavers (Ploceus cucullatus) at the Amurum Forest Reserve, Nigeria. We compared four groups (n = 148 total) sampled within 3 mins post-capture: infected-moulting (IM), infected-non-moulting (IN), non-infected-moulting (NM), and non-infected-non-moulting (NN). Physiological condition was assessed using the erythrocyte glutathione ratio (GSH:GSSG) and circulating glucose, while plumage reflectance traits were integrated into a composite quality axis (PC1). Microfilarial infections were present in 52.0% (n = 77) of individuals; mean parasite intensities were 6.13 ± 0.35 mf/µL (IN) and 6.45 ± 0.41 mf/µL (IM). Physiological indices varied strongly across groups. The GSH:GSSG ratio was reduced in infected birds, indicating altered redox balance (rs = −0.65). Circulating glucose was highest in the infected non-moulting group (IN) but substantially reduced in the infected moulting group (IM). Across physiological and ornamental traits, individuals experiencing both infection and moult (IM group) exhibited the strongest reductions relative to all other groups. However, this pattern reflects a statistically supported Infection × Moult interaction, rather than an untested synergistic or non-linear effect, as evidenced by significant IN vs. IM contrasts in glucose (Table 3; z = 33.43, P < 0.0001, d = 6.10) and plumage quality. This interaction was associated with reduced plumage hue and lower integrated signal quality. Our results suggest that microfilarial infection and moult impose overlapping physiological demands that constrain metabolic regulation and the expression of carotenoid-based ornaments. Intracellular redox balance emerges as a potential mechanistic link between physiological state and ornamental expression, supporting the hypothesis that village weaver plumage reflects variation in sustained physiological condition under natural ecological stress.